Environmental Management of Equine Asthma - Elisa Diez de Castro; Jose Maria Fernandez-Molina (Animals, 2024)
Environmental practices related to the inhalation of airborne dust have been identified as the main cause of equine asthma (EA) and reasonably, they are truly relevant in its treatment and control, especially for horses with its severe form. Vast research regarding environmental recommendations has been conducted in recent years. However, no recent exhaustive reviews exist that gather all this new evidence. The aim of this review is to report and compare the most pertinent information concerning the environmental management of EA. The main findings highlight the importance of the type of forage used for feeding but also its method of production and possible contamination during manufacture and/or storage. Procedures to reduce this, such as soaking and steaming hay, improve its hygienic quality, although they also decrease forage’s nutritional value, making dietetic supplementation necessary. Regarding stabling, despite some conflicting results, avoiding straw as bedding and improving barn ventilation continue to be the common recommendations if turning to pasture is not feasible. Finally, owners’ compliance has been identified as the most critical point in correct environmental control. Educating owners about the genuine benefits of these measures should be a cornerstone of EA management.